1998
DOI: 10.1016/s0042-6989(97)00142-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fixation disparities obtained by objective and subjective methods

Abstract: Fixation disparities (FD) were measured as a function of forced vergence using binocular scleral search coils and simultaneously with nonius lines. The slope of the objective FD curve was significantly greater than the subjective FD curve for three of five subjects. This indicates an alteration in retinal correspondence of up to one degree, that shifts Panum's area to avoid the diplopia normally present with large disparities. This process allows for fusion in the presence of large objective fixation dispariti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(79 citation statements)
references
References 19 publications
1
78
0
Order By: Relevance
“…This was probably due to a lack of compliance on their part to fixate each of the calibration stimuli properly. Indeed, eye-tracking is always subject to some uncertainty that can be described by a standard deviation due to the calibration (SDc) [22].Generally, each calibration run included a routine to address this uncertainty (for further examples, see [23], [24]) and for the present data we excluded blocks of trials which showed a SDc larger than 10 arcmin. Thus, the sample size was further reduced to 9 and all subsequent analyses were performed on this subsample only.…”
Section: Methodsmentioning
confidence: 99%
“…This was probably due to a lack of compliance on their part to fixate each of the calibration stimuli properly. Indeed, eye-tracking is always subject to some uncertainty that can be described by a standard deviation due to the calibration (SDc) [22].Generally, each calibration run included a routine to address this uncertainty (for further examples, see [23], [24]) and for the present data we excluded blocks of trials which showed a SDc larger than 10 arcmin. Thus, the sample size was further reduced to 9 and all subsequent analyses were performed on this subsample only.…”
Section: Methodsmentioning
confidence: 99%
“…(1986), Robertson and Schor (1986), Regan et al. (1990), and Fogt and Jones (1998a) also suggested that the discrepancy between objective and subjective fixation disparity increases with the amount of forced vergence. Consequently, objective and subjective measures of fixation disparity could be similar if vergence is not in a forced state, as was concluded by Howard (2002, p. 379).…”
Section: Introductionmentioning
confidence: 97%
“…However, research has shown examples of discrepancies between subjective and objective vergence measures; see reviews of Howard (2002) and Howard and Rogers (2002). For example, it has been found that nonius lines do not indicate the full amount of fixation disparity under forced vergence (Fogt and Jones, 1998a,b) and do not measure periodical dynamic vergence changes (Erkelens and van Ee, 1997a,b). From results under these conditions, it was concluded that the visual direction of monocular nonius lines is influenced by closely adjacent fusion stimuli.…”
Section: Introductionmentioning
confidence: 99%